Ornamental potential of species from the ferruginous Campo rupestre of the Carajás National Forest, Brazilian Amazon - Sousa, Renata Paschoal da Silva; Costa, Wendelo Silva; Matos, Paula e Silva; Carvalho, Andréa Siqueira; Martins, Frederico Drumond; Torres, Kátia Ribeiro (Comunicata Scientiae, 2020)
The flora of the ferruginous Campo rupestre that occur over the immense iron deposits of the Carajás National Forest is very unique, with several endemic and rare species. This vegetation is directly affected by mining activity, as a result of vegetation suppression and the profound disfigurement of habitats. The objective of this work was to identify the ornamental potential of the flora of the ferruginous Campo rupestre, as a strategy for ex situ conservation of ecosystem species. The species present in ten plots of 5 x 5 m were surveyed in different areas of the ferruginous Campo rupestre on the N1 plateau and the ornamental potential of each species was evaluated following a characterization key, considering morphology and habitat of occurrence. Subsequently, the species were compared with those already present on the market, as ornamental, based on the literature and on sites specialized in the sale of ornamental plants in Brazil. A total of 33 species with ornamental potential were found, distributed in 32 genera and 19 families. Most species showed high functionality for ornamentation and similarity with nationally consolidated ornamentals. Catasetum planiceps, Cyrtopodium andersonii, Epidendrum nocturnum, Mandevilla scabra, Norantea guianensis and Sobralia liliastrum have a consolidated ornamental market. The data collected support ex situ conservation strategies of the flora of the ferruginous Campo rupestre, such as its valorization, local commercialization and income generation for small extractivists in the region.